Career Development Among Chinese Women in the Banking Sector in New Zealand - Lam, Cynthia (Cynthia Po Yee) (Auckland University of Technology, 2006)
The banking industry is highly competitive in New Zealand. As the number of Chinese-speaking immigrants has increased dramatically over the last two decades, banks have realized a demand for native Chinese-speaking staff with banking experience. This situation makes opportunities available for Chinese-speaking individuals. The opportunities are often branch-based customer service positions or operational positions in processing centres that are not necessarily indicators of career progression. The aim of this study was to undercover the working experiences of Chinese women who work in banks in New Zealand as this is an under-researched area and there is a need to address issues that Chinese women face in labour force in New Zealand. This study will attempt to investigate career development among Chinese women in the banking sector in New Zealand through qualitative semi-structured interviews. Previous studies in career development attempted to create theory by looking at an individual’s experience over a certain period of time. This study takes a different research approach by gathering in-depth qualitative information from participants. Ten participants were selected by the snowball technique to participate in this study, and while the interviews were done in a relaxed environment, the interview protocol which included a series of open ended questions, served to focus the interviews on career development as experienced by these Chinese women. Traditionally, research in career development has been based on the life span of white male white-collar workers and such research has defined different career stages and job performances. However women’s careers have evolved differently. Many women may perceive their sex as a disadvantage to further career development and have experienced sex discrimination in their workplace often leading to the glass ceiling effect. In the workforce, women not only face gender equity issues, but also have been found to have more work-life balance issues than men. Gender equity issues and work-life balance issues could lead to individual pressures. Where Chinese women are concerned, ethnically is an additional factor besides gender, particularly since Chinese are a minority ethnic group in New Zealand. Hence, there may be other possible pressures in terms of social interaction with different cultures and communication issues. The participants in this study have addressed several issues in their perception of the New Zealand workforce. Whilst they enjoy the lifestyle and the environment in New Zealand, most of them saw it as a trade-off towards their career progression. The Chinese women also raised issues such as underemployment, under representation at management level, glass ceiling and issues in social fit. This research is useful in many aspects, it is particularly relevant to new immigrants, people thinking of migrating, Chinese women (first, second and third generations) who want to switch careers, banks for recruitment purposes, recruitment agencies, students who wish to gain a better understanding of immigrants’ career development in New Zealand and researchers who wish to develop other generalization or theoretical researches into similar topics of ethnicity and careers both in New Zealand and abroad.
Keywords: Banks and banking -- Personnel management -- New Zealand; Financial services industry -- Personnel management -- New Zealand; Women bankers -- New Zealand; Women bank employees -- New Zealand; Women in finance -- New Zealand; Chinese -- New Zealand -- Employment; Minority women -- New Zealand -- Employment